(untitled) (Archaeologia Adriatica, 2022)
This contribution presents the results of the bioarchaeological analysis of human skeletal remains from excavations at the Nadin necropolis, focusing on the reconstruction of population demographics and pathological conditions. This site has represented a methodological challenge for traditional individual-level skeletal analyses because the primary architectural unit in the necropolis, parcela, contain commingled and fragmentary elements with evidence of repeated use, multiple inhumations, and cremations. Therefore, landmark-based methods for the determination of MNI have been applied in the analysis of skeletal remains from the 2013 and 2015 excavations. This allowed a more accurate construction of the demographic profile for the site in combination with estimates from previous reports. The minimum number of individuals for the Nadin necropolis, combined with the previously published MNI from within the space delineated as parcela (“cela”) 1 (n=45), is estimated to be 196. These data also show a higher count of subadult remains (51%, n=99), compared to reports for other Iron Age sites in the region. Based on paleodemographic evaluations of the connections among younger age cohorts in skeletal collections, fertility, and population size, high infant and child mortality suggest population growth.